2007
DOI: 10.1080/07357900701209103
|View full text |Cite
|
Sign up to set email alerts
|

Serum Lactate Dehydrogenase Level is a Prognostic Factor in Patients with Locoregionally Advanced Nasopharyngeal Carcinoma Treated with Chemoradiotherapy

Abstract: We investigated the treatment results and probable prognostic factors in patients with locoregionally advanced nasopharyngeal carcinoma (NPC) treated with neoadjuvant chemotherapy (NCT) plus conventional radiotherapy (RT) or concomitant chemoradiotherapy (CCRT) at our hospital. We retrospectively evaluated 61 patients (48 males, 13 females) with locoregionally advanced NPC treated either with 2 cycles of NCT plus RT (Group A, 37 patients) or with three cycles of NCT plus CCRT (Group B, 24 patients) between Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 29 publications
2
28
0
1
Order By: Relevance
“…Several studies have shown that serum LDH may be an ominous prognostic marker in malignant tumors [24], i.e. serum LDH is a prediction factor for the response of chemotherapy in patients with locoregionally advanced nasopharyngeal carcinoma [25] and advanced oesophageal cancer [26]. Elevated serum LDH also showed correlation with survival time of terminally ill cancer patients [27] and with the clinical stage of lung cancer [28].…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have shown that serum LDH may be an ominous prognostic marker in malignant tumors [24], i.e. serum LDH is a prediction factor for the response of chemotherapy in patients with locoregionally advanced nasopharyngeal carcinoma [25] and advanced oesophageal cancer [26]. Elevated serum LDH also showed correlation with survival time of terminally ill cancer patients [27] and with the clinical stage of lung cancer [28].…”
Section: Discussionmentioning
confidence: 98%
“…LDH5 is upregulated in cancers (Koukourakis et al 2005a) which ensures continued glycolysis irrespective of the oxygen concentration (Dang and Semenza 1999;Robey et al 2005;Schulz et al 2006). Elevated serum LDH levels have been shown to correlate with poor prognosis in patients with pancreatic, renal, nasopharyngeal, and lung carcinoma amongst others (Tas et al 2001a, b;Turen et al 2007;Motzer et al 1999).…”
Section: Pfk-1mentioning
confidence: 97%
“…All these uncertainties highlighted the necessity of additional investigation in prospective setting. With further research into other predicting factors of NPC, such as tumour volume (21), serum lactate dehydrogenase (22), comorbidity (23) and Epstein-Barr virus Deoxyribonucleic acid (EBV-DNA) (24)(25)(26) and other molecular prognostic markers, it is likely that these will be taken in conjunction with stage classification in grouping patients into different prognostic groups, each with different recommended treatment. This kind of approach has been adopted for patients with human papillomavirus-related oropharyngeal carcinoma, as have been reported by Huang et al (27) from Canada.…”
Section: Discussionmentioning
confidence: 99%